2001
DOI: 10.1061/(asce)0733-947x(2001)127:1(82)
|View full text |Cite
|
Sign up to set email alerts
|

Soil Friction Restraint of Oblique Pipelines in Loose Sand

Abstract: This paper presents the soil friction restraint on the oblique pipelines in loose sand. A series of experimental tests are conducted in a prefabricated large scale drag box with dimensions 1.83 m × 1.83 m × 1.22 m. Model pipes 0.61 m long with diameters of 152.4, 228.6, and 304.8 mm are obliquely moved from an axial-longitudinal to lateral-transversal direction in the drag box to study the associated soil restraints of the oblique pipes with various shallow embedded depths. All the test results indicate that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The design of pipelines to withstand the effects of large reverse fault displacements warrants inclusion of improved soil restraint boundary conditions that account for the reduction of vertical soil restraint as the pipe ploughs generally parallel to the fault dip plane (obliquely) through the backfill toward the ground surface. Except for a limited work addressing the problem of pipelines crossing faults (e.g., Hsu et al 2006;Hsu et al 2001;Jung et al 2016;Saiyar et al 2016;O'Rourke et al 2016), currently, there is a general absence of public literature relating to oblique soil restraint relationships, particularly relationships that have been validated by appropriate full-scale testing. To alleviate this gap in knowledge, a series of full-scale oblique-displacement pipe-soil interaction model tests have been undertaken at the University of British Columbia (UBC) Advanced Soil Pipe Interaction Research (ASPIRe TM ) laboratory.…”
Section: R a F Tmentioning
confidence: 99%
“…The design of pipelines to withstand the effects of large reverse fault displacements warrants inclusion of improved soil restraint boundary conditions that account for the reduction of vertical soil restraint as the pipe ploughs generally parallel to the fault dip plane (obliquely) through the backfill toward the ground surface. Except for a limited work addressing the problem of pipelines crossing faults (e.g., Hsu et al 2006;Hsu et al 2001;Jung et al 2016;Saiyar et al 2016;O'Rourke et al 2016), currently, there is a general absence of public literature relating to oblique soil restraint relationships, particularly relationships that have been validated by appropriate full-scale testing. To alleviate this gap in knowledge, a series of full-scale oblique-displacement pipe-soil interaction model tests have been undertaken at the University of British Columbia (UBC) Advanced Soil Pipe Interaction Research (ASPIRe TM ) laboratory.…”
Section: R a F Tmentioning
confidence: 99%
“…While there are many stud ies in the literature investigating the lateral-vertical pipe-soil interaction, there are a limited number of studies on axial-lateral pipe-soil interaction, and the authors could not find any study on axial-vertical pipe-soil interaction events. Hsu et al (2001Hsu et al ( , 2006 investigated the axial-lateral pipesoil interaction for shallow buried pipes in loose and dense sand. Large-scale tests were conducted for 10 different angles of movement (q) between 0° and 90° ( Fig.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…Several soil spring models have been proposed the last decades on the basis of experimental and numerical studies, to account for the soil compliance on buried pipelines in both the axial and the horizontal transverse directions (O' Rourke M.J. and Wang, 1978;Selvadurai, 1985;El Hmadi and O'Rourke M.J., 1988). Other studies provided relations for the evaluation of the ultimate soil resistance forces to lateral, vertical or oblique pipeline movements (Audibert and Nyman, 1977;Nyman, 1984;O'Rourke M.J. and El Hmadi, 1988;Hsu et al, 2001). A rather detailed summary of these studies may be found in .…”
Section: Beam or Shell Element Pipe Models On Soil Springsmentioning
confidence: 99%